Genome-Wide and Phenotypic Evaluation of Stem Cell Progenitors Derived From Gprc5a-Deficient Murine Lung Adenocarcinoma With Somatic Kras Mutations - Daouk, Reem; Hassane, Maya; Bahmad, Hisham F.; Sinjab, Ansam; Fujimoto, Junya; Abou-Kheir, Wassim; Kadara, Humam (Frontiers in Oncology, 2019)
Lung adenocarcinomas (LUADs) with somatic mutations in the KRAS oncogene comprise the most common molecular subtype of lung cancer in smokers and present with overall dismal prognosis and resistance to most therapies. Our group recently demonstrated that tobacco carcinogen-exposed mice with knockout of the airway lineage G-protein coupled receptor, Gprc5a, develop LUADs with somatic mutations in Kras. Earlier work has suggested that cancer stem cells (CSCs) play crucial roles in clonal evolution of tumors and in therapy resistance. To date, our understanding of CSCs in LUADs with somatic Kras mutations remains lagging. Here we derived CSCs (as spheres in 3D cultures) with self-renewal properties from a murine Kras-mutant LUAD cell line we previously established from a tobacco carcinogen-exposed Gprc5a-/- mouse. Using syngeneic Gprc5a-/- models, we found that these CSCs, compared to their parental isoforms, exhibited increased tumorigenic potential in vivo, particularly in female animals. Using whole-transcriptome sequencing coupled with pathways analysis and confirmatory PCR, we identified gene features (n = 2,600) differentially expressed in the CSCs compared to parental cells and that were enriched with functional modules associated with an augmented malignant phenotype including stemness, tumor-promoting inflammation and anti-oxidant responses. Further, based on in silico predicted activation of GSK3β in CSCs, we found that tideglusib, an irreversible inhibitor of the kinase, exhibited marked anti-growth effects in the cultured CSCs. Our study underscores molecular cues in the pathogenesis of Kras-mutant LUAD and presents new models to study the evolution, and thus high-potential targets, of this aggressive malignancy.